The secreted endoribonuclease ENDU-2 from the soma protects germline immortality in C. elegans - Wenjing Qi (Nature Portfolio, 2021)
The question as to how the soma regulates the germline has been much studied. Here, the authors show in C. elegans that the poly-U specific endoribonuclease ENDU-2 is secreted from the soma and taken-up by the germline, binding mature mRNA, repressing expression of somatic transcripts and maintaining germline immortality.